Paving the Path to Green Mobility: An Analysis of Price, Knowledge, and Value Perception on E-Bike Purchase Intentions in Pekanbaru City - Sari, Mayang; Wijayanto, Gatot; Siregar, Prima Andreas (Westscience Press, 2025)
This study was conducted with the aim of knowing the effect of product knowledge and price on perceived value and purchase intention of Uwinfly electric bicycles in Pekanbaru City. The population in this study were people in Pekanbaru City who were familiar with electric bicycles. Sampling was carried out using non-probability sampling techniques, with a sample size of 130 respondents based on the formula Hair et al. (2023). The data analysis method used is Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS software version 4. The results showed that product knowledge has no significant effect on purchase intention, but price has a significant positive effect on purchase intention. In addition, product knowledge and price have a positive effect on perceived value, where perceived value acts as a mediator in the relationship. These findings provide important implications for Uwinfly in designing more effective marketing strategies to increase consumer purchase intention.